Column curves for stainless steel-lipped channel sections - Dobrić, J; Rossi, B (American Society of Civil Engineers, 2020)
The strength of thin-walled stainless steel columns has been investigated extensively over the last few years. The present paper presents the results of an extensive computational study of the buckling strength of lipped–channel section columns made of austenitic, duplex, and ferritic grades. The numerically computed strengths together with the available experimental data collected in the literature are compared to the current European and Australian/New Zealand standard (AS/NZS) codified predictions over the whole slenderness range. Minor and major axis buckling as well as flexural-torsional buckling are considered. A reliability assessment in the sense of both standards is then performed. The safety factor γm and resistance factor ϕc are computed per family of stainless steel. In conclusion, we advise the use of different European buckling column curves rather than the one currently adopted in the code and to make a distinction between the families of stainless steel. Besides, seeing the very good agreement found against the AS/NZS guidance, we propose that the factor η, currently being a linear expression in the European standard, be replaced by the AS/NZS expression with the proposed parameters for each stainless steel family.